Microsoft SQL Server 2000 bible - Nielsen, Paul (Wiley pub, 2003)
Organization: The book is divided into 6 parts: Preparing to Develop with SQL Server; Building and Managing Databases with SQL Server; Managing Data with SQL Server; Implementing Business Rules with SQL Server; Monitoring and Performance Tuning with SQL Server; and Advanced Data Transfer and Analysis with SQL Server